Teorija i praktika rossijskogo dzjudo: kakovy perspektivy integracii? - Sijan, V. V.; Nevzorov, V. M. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The essentially various understanding of the physiological mechanisms which lie in the basis of the development of special endurance wrestlers, has caused two contradictory concepts of construction of the educational-training process of judoists at the final stage of the training for the major competitions. The authors offer not only the detailed analysis of these approaches, but also support it with the results of their own researches.